Pojok Literasi-Ku Berbasis Pendidikan Masyarakat Sebagai Upaya Meningkatkan Kesadaran Literasi di Desa Bumi Sari Kabupaten Nagan Raya Aceh - Rahmayanti Tambunan; Nellis Mardhiah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity aims to increase the literacy awareness of the residents of Bumi Sari Village, Nagan Raya Regency, through a community education-based My Literacy corner. The method of implementing this service used mentoring and teaching. Partners in this service were the Nagan Raya Library Service, the Nagan Raya Education Office, the Environmental Care Alliance (APEL), the Communication, Informatics, and Statistics Service (KOMINFOTIK), and the Bumi Sari Village Government. The instrument used to measure the success of this community service activity was in the form of a questionnaire given to each person in charge of the literacy corner. This dedication resulted in implementing five literacy corner programs in Bumi Sari Village: Reading Corner, Writing Corner, Internet Introduction Corner, Computer Training Corner, and MS Introduction Corner Office. There was an increase in literacy among the people of Bumi Sari Village by 36.35%. This increase could be seen from the number of people before the activity, where only 34.41% understood literacy, then it increased to 70.76% after this community service activity. The response of the people of Bumi Sari Village, especially the parents, towards the literacy corner program was very good, judging from the number of children participating in learning in the literacy corner. This service activity could increase literacy awareness in Bumi Sari Village.